Teknik Pembuatan Peta Administrasi Pada Kota Kuala Simpang, Kabupaten Aceh Tamiang - M Aulia; B Karsono; A Dela (Cered Indonesia Institute, 2024)
Kuala Simpang City is located in Kuala Simpang District, Aceh Tamiang Regency. However, Kuala Simpang City does not yet have a digital administrative area map or a map that can be installed at the location. The method used is a GIS mapping application using ArcGIS 10.8 software. These results produce several administrative maps that are needed for the development and development of Kuala Simpang City, especially Kuala Simpang City. The city needs an administrative map database to help determine development plans for the coming year. Clear city boundaries help determine the amount of revenue from mining and land managemen.